2022
DOI: 10.1097/wco.0000000000001085
|View full text |Cite
|
Sign up to set email alerts
|

Lesion network mapping for symptom localization: recent developments and future directions

Abstract: Purpose of reviewFocal lesions causing specific neurological or psychiatric symptoms can occur in multiple different brain locations, complicating symptom localization. Here, we review lesion network mapping, a technique used to aid localization by mapping lesion-induced symptoms to brain circuits rather than individual brain regions. We highlight recent examples of how this technique is being used to investigate clinical entities and identify therapeutic targets. Recent findingsTo date, lesion network mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…17 Growing research has demonstrated that many disorders map to broad brain networks more than specific regions. 18 Recently, Joutsa et al 19 used lesion network mapping to investigate the functional connectivity of dispersed brain lesions that relieved ET symptoms. All lesion locations were functionally connected to the cerebellum and thalamus, thus revealing a common network mediating tremor relief defined by connectivity to key hubs in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…17 Growing research has demonstrated that many disorders map to broad brain networks more than specific regions. 18 Recently, Joutsa et al 19 used lesion network mapping to investigate the functional connectivity of dispersed brain lesions that relieved ET symptoms. All lesion locations were functionally connected to the cerebellum and thalamus, thus revealing a common network mediating tremor relief defined by connectivity to key hubs in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…By this simple association or correspondence, LNM has been capable of explaining the presence or absence of a similar symptom within a clinical cohort, depending on whether or not the patients' lesions are connected to a common network. Importantly, a recent review has shown that while LSM was not sufficient to explain motor, non-motor, sensory and behavioral changes after brain damage, LNM successfully explained a total of 40 different changes 52 , relating symptoms to lesions connected to a common network, and where more often than not, the location of the lesion alone (the gold standard in clinical practice) was not able to explain these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Further adjustment for potential confounders was not possible due to the small number of subjects with overlap. Future studies in larger datasets and the use of alternative mapping methods such as lesion network mapping that allows for localization of symptoms to brain circuits rather than individual brain lesions could help better understand the causality 51 …”
Section: Discussionmentioning
confidence: 99%